Complementarity and the Discount Rate for Public Investment - Burgess, David F. (Quarterly Journal of Economics, 1988)
The marginal rate of return on public investment in a tax-distorted economy is a weighted average of the marginal social productivity of capital in the private sector and the marginal social rate of time preference, but the weights are shown to depend not only on the proportions of funding obtained from each source through incremental borrowing but also on the degree of complementarity or substitutability between public and private investment.